An association between cancer type and delirium incidence in Japanese elderly patients: A retrospective longitudinal study. (26th July 2022) - Yamato, Kentaro; Ikeda, Ai; Endo, Motoki; Filomeno, Ronald; Kiyohara, Kosuke; Inada, Ken; Nishimura, Katsuji; Tanigawa, Takeshi
Abstract: Objective: There is not a known elevated prevalence of delirium in older adult cancer patients. However, it is unknown if the incidence of delirium varies by cancer type among older adult patients. Therefore, this study aimed to examine the association between the incidence of delirium and cancer type among older adult patients using a Japanese hospital‐based administrative claims database. Methods: A total of 76, 868 patients over 65 years of age or older, first diagnosed with cancer on an initial date of hospitalization between April 2008 and December 2019, were included in this retrospective longitudinal study. Delirium was defined by the World Health Organization's International Statistical Classification of Diseases and Related Health Problems (ICD‐10) codes or antipsychotic medication use. Cox proportional hazard models were performed to estimate the risk of delirium incidence according to 22 cancer types during the one‐year hospitalization period. Results: The incidence rates of delirium were 17.1% for men and 15.3% for women. Compared to gastric cancer, the risk of delirium was significantly higher for pancreatic cancer (HR: 1.26, 95% CI: 1.11–1.42 for men; HR: 1.27, 95% CI: 1.11–1.45 for women), leukemia (HR: 1.24, 95% CI: 1.09–1.41 for men; HR: 1.20, 95% CI: 1.03–1.41 for women), and oropharyngeal cancer (HR: 1.30, 95% CI: 1.10–1.54 for men; HR: 1.32; 95% CI: 1.02–1.72 for women) after adjusting for age, initial hospitalization year, antipsychotic medications, and surgery. Conclusions: As compared to gastric cancer, patients with pancreatic cancer, leukemia, oropharyngeal cancer were found to have a higher risk of developing delirium. Our study findings suggested that the risk of delirium incidence may vary by cancer type. Abstract : The incidence rates of delirium were 17.1% for men and 15.3% for women with cancer. Compared to gastric cancer, the risk of delirium was significantly higher for pancreatic cancer, leukemia, and oropharyngeal cancer.